ORIENTASI BUDAYA DAN RELIGIUSITAS DALAM MANAJEMEN KREDIT SERTA DAMPAKNYA TERHADAP KINERJA SOSIAL BANK PERKREDITAN RAKYAT - Puteri, Hesi Eka; Zuwardi, Zuwardi (LLDIKTI Wilayah X, 2019)
This study investigates the implementation of culture and religiosity in credit management and then attempts to analyze the effect of culture and religiosity to the breadth of outreach in Rural Banks. This research is a quantitative study based on a survey at Rural Banks in West Sumatera Indonesia in 2018, with a sample of 52 Rural Bank. Data were collected by using questionaire and analyzed by PLS-regression.. The independent sample t-test also applied to compare the breadth of outreach or social performance in Conventional Rural Banks and Islamic rural banks. This study proves that the breadth of outreach is influenced by culture and religiosity and there is no difference of the breadth of outreach between Conventional Rural Bank and Islamic Rural Bank. These finding extends the predictor of the breadth of outreach in Rural Banks and offer a more established model of causal relationships between culture and religiosity to the breadth of outreach. This study also proves that there is no difference in the breadth of outreach between Conventional Rural Banks and Islamic Rural Banks, which means that there are no differences in the achievement of the social performance of these two types of micro financial institutions. Penelitian ini menganalis implementasi aspek budaya dan religiusitas dalam manajemen kredit untuk kemudian mengelaborasi lebih lanjut pengaruh faktor budaya dan religiusitas terhadap keluasan jangkauan Bank Perkreditan Rakyat (BPR). Penelitian ini merupakan penelitian kuantitatif berdasarkan survey pada BPR-BPR di Provinsi Sumatera Barat Indonesia pada tahun 2018, dengan sampel sebanyak 52 BPR. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis dengan Regresi PLS untuk memprediksi dampak budaya dan religiusitas terhadap keluasan jangkauan. Uji-independent sample t -test juga diterapkan untuk membandingkan keluasan jangkauan BPR Konvensional dan BPR Syariah. Penelitian ini membuktikan bahwa keluasan jangkauan dipengaruhi oleh budaya dan religiusitas dan tidak ada perbedaan keluasan jangkauan antara BPR Konvensional dan BPR Syariah. Temuan ini memperluas prediktor keluasan jangkauan di Bank Perkreditan Rakyat dan menawarkan model hubungan sebab akibat yang lebih mapan antara budaya dan religiusitas terhadap keluasan jangkauan. Penelitian ini juga membuktikan bahwa tidak ada perbedaan keluasan jangkauan antara BPR Konvensional dan BPR Syariah, yang berarti tidak ada perbedaan dalam pencapaian kinerja sosial kedua jenis lembaga keuangan ini.